2010
DOI: 10.1371/journal.pone.0013864
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Acidification Drives S. pyogenes Pilus Expression and Microcolony Formation on Epithelial Cells in a FCT-Dependent Manner

Abstract: Group A Streptococcus (GAS, Streptococcus pyogenes) is a Gram-positive human pathogen responsible for a diverse variety of diseases, including pharyngitis, skin infections, invasive necrotizing fasciitis and autoimmune sequelae. We have recently shown that GAS cell adhesion and biofilm formation is associated with the presence of pili on the surface of these bacteria. GAS pilus proteins are encoded in the FCT (Fibronectin- Collagen-T antigen) genomic region, of which nine different variants have been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 57 publications
(89 reference statements)
3
64
0
Order By: Relevance
“…Recently, site-directed mutagenesis suggested that LiaS may contribute to extracellular acidification and may be activated under acidic conditions, and this directly affected biofilm formation (44). Further, GAS pili contribute to biofilm formation, and, at least for a subset of FCT types, a lower environmental pH enhances pilus gene transcription (45). More studies are needed to further define the precise mechanism of pilus gene regulation by LiaFSR and the mechanism by which the liaS R135G carrier mutation alters pilus gene transcription.…”
Section: Fig 5 Elimination Of Pilus In Mgas10870 Liasmentioning
confidence: 99%
“…Recently, site-directed mutagenesis suggested that LiaS may contribute to extracellular acidification and may be activated under acidic conditions, and this directly affected biofilm formation (44). Further, GAS pili contribute to biofilm formation, and, at least for a subset of FCT types, a lower environmental pH enhances pilus gene transcription (45). More studies are needed to further define the precise mechanism of pilus gene regulation by LiaFSR and the mechanism by which the liaS R135G carrier mutation alters pilus gene transcription.…”
Section: Fig 5 Elimination Of Pilus In Mgas10870 Liasmentioning
confidence: 99%
“…Among the various serotype strains, serotype M6 strains produce high levels of biofilm in vitro, regardless of culture conditions (23,32). To evaluate whether FCT type 1 pili are necessary for biofilm formation, wild-type and mutant strains were grown in C medium, and the ability to form biofilm on polystyrene plates was assessed by crystal violet staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, several GAS factors, including transcriptional regulators, have been reported to promote or attenuate biofilm formation (7,10,12,27,29,51); thus it is likely that such formation is a multifactorial event. However, our recent epidemiological studies clearly showed associations between several FCT types and the capability to form biofilms (23,32,43,44). …”
mentioning
confidence: 94%
See 1 more Smart Citation
“…FCT type 9 isolates were poor biofilm producers, while FCT type 3 and 4 isolates were unequally and irregular biofilm producers. Manetti et al [44] demonstrated association between biofilm formation among FCT types 2, 3, 5, 6 and FCT subset 4 in acidic surroundings.…”
Section: Biofilmmentioning
confidence: 99%